Analysis of the Creep Behaviour of Poly(Methyl Methacrylat) - José, André (2002)
Previous models for the interpretation of the creep behaviour of polymers are mainly empirical or semi-empirical, and do not take into direct account the physical (molecular) underlying mechanisms responsible for the material’s non-linear viscoelastic behaviour. In the present study, a physical model is developed to describe the creep compliance of polymer materials (applicable to both amorphous and semi-crystalline polymers), at varying tensile stresses and ambient temperatures.